Genotype and environmental interactions in Maize (Zea mays L.) across regions of India: implications for hybrid testing locations in South Asia - Nagesh, Patne; Takalkar, Satish Ashok; Mohan, Sagala Murali; Naidu, Pulime Bhaskara; Lohithaswa, Hirenallur Chandappa; Kachapur, Rajashekhar M.; Kuchanur, Prakash; Injeti, Sudhir Kumar; Singh, Narendra Kumar; Kanwade, Dinesh G.; Shrestha, Jiban; Vivek, Bindiganavile (Southern Cross Journals, 2025)
Maize in South Asia is primarily rainfed and is particularly vulnerable to the changing climate. Defining a breeding environment (product profile/market segment) is the first key step of any breeding program. Further, identifying discriminative and representative locations for hybrid evaluation ensures efficiency and cost optimization. Therefore, this study was an extensive evaluation of elite maize hybrids across 12 locations in India to determine the G×E interactions in order to identify representative sites for CIMMYT product profiles for gaining resource efficiency while achieving enhanced genetic gains. Twenty-one promising hybrids that had been identified to be either drought-tolerant, excess moisture tolerant or heat tolerant through a stage-gate process, were planted as an Alpha lattice during the rainy season of 2017, spanning 12 locations in India. GGE biplot analysis was used to determine the top-performing hybrids and more importantly to discern the most representative environments. Hybrids VH151139 and VH131376 were found to be highly promising (and stable across locations) hybrids for grain yield in the main cropping season. Ideal test location/s for selecting superior maize hybrids were identified and ranked based on their grain-yielding and discriminating potential. The grouping of the locations based on the environmental vector biplot, identified location Meerut (E3) in the first group to represent areas prone to excess moisture. Bheemarayanagudi (E5) was in the second group representing drought-prone areas; and locations Nadiad (E6), Kalol (E9), and Wadadhe (E10) were in the third group where crops face drought and heat stress in the same season. Consequently, these locations should be consistently utilized for the selection of stable hybrids. The findings from this study have implications for similar and wider stress-prone maize growing agroecologies covering South and South-East Asia. Expanding the testing across similar regional locations will enhance the reach of CIMMYT's Asia breeding program which presently targets approximately 6.3 million hectares.